FOREIGN FORMS, METHODS AND TOOLS OF REORGANIZATION OF A CREDIT INSTITUTION - Z. Patladze (Вестник университета)
In the article on the example of the United States of America, The United Kingdom of Great Britain and Northern Ireland, France and Germany, are considered foreign forms, methods and tools for the reorganization of a credit institution, draws conclusions about the possibility of using the experience of these countries in the Russian Federation.